2005
DOI: 10.1159/000089689
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria and Fusion of Podocyte Foot Processes in Rats after Infusion of Cytokine from Patients with Idiopathic Minimal Lesion Nephrotic Syndrome

Abstract: Background/Aims: We report on the isolation of a factor secreted by peripheral blood mononuclear cells from patients with idiopathic minimal lesion nephrotic syndrome (IMLNS) in relapse and its effect on proteinuria and podocyte morphology in the rat. Methods: Peripheral blood mononuclear cells from patients with IMLNS (in relapse and in remission) and patients with focal segmental glomerulosclerosis were cultured for 72 h. Supernatants from 20 × 106 cultured cells were separated by liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…PBMC were isolated by density centrifugation on a Ficoll-Hypaque gradient as previously described [11] and cultured in 5 ml of RPMI (Grand Island Biological, Grand Island, NY, USA) supplemented with 10% fetal bovine serum (FBS) in Petri dishes for 72 h at 35°C, at a concentration of 1×10 6 cells/ml [4]. At the end of the incubation time supernatants were collected and concentrated 1.5- to 9-fold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBMC were isolated by density centrifugation on a Ficoll-Hypaque gradient as previously described [11] and cultured in 5 ml of RPMI (Grand Island Biological, Grand Island, NY, USA) supplemented with 10% fetal bovine serum (FBS) in Petri dishes for 72 h at 35°C, at a concentration of 1×10 6 cells/ml [4]. At the end of the incubation time supernatants were collected and concentrated 1.5- to 9-fold.…”
Section: Methodsmentioning
confidence: 99%
“…Injection into rats of supernatants from the T-cell hybridoma from patients in relapse caused immediate proteinuria and glomerular podocyte foot process fusion, whereas no changes were noted when the T-cell hybridoma supernatants from healthy controls were infused [3]. Proteinuria has also been reported when supernatants from cultures of peripheral blood mononuclear cells (PBMC) from MCD patients in relapse were infused into rats [4]. However, despite numerous efforts over the last 30 years, the pathogenic cytokine has not been identified and the mechanism of proteinuria in these patients has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A specific pathogenic cytokine has not yet been identified, but several cytokines known to be elevated in the serum of patients with IMLNS during relapse have been shown to increase glomerular permeability to plasma proteins, among them interleukin (IL)-8 [3], 100 kDa glycoprotein [4], IL-13 [5], and a cytokine described by Koyama et al [6]. These latter authors were able to immortalize T cells from patients with IMLNS and show that the T cell culture supernatants could induce massive proteinuria in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whether our conclusion can be generalized to other MCD animal models like lipopolysaccharide-induced MCD as well as human MCD is questionable [25]. For instance, some investigators using clinical observation argued that there was no causal relationship between foot process effacement and proteinuria [26, 27], though most preclinical studies on MCD showed that the 2 factors were associated with each other [9, 28, 29]. The success of calcineurin inhibitors such as cyclosporine A and FK506 in clinical practice suggested that the activation of calcineurin in human MCD patients may be true and thus showed a bright future [21].…”
Section: Discussionmentioning
confidence: 99%